Benefits of Therapeutic Drug Monitoring of First Line Antituberculosis Drugs - Prso K; Zidekova N; Dohal M; Porvaznik I; Prso M; Kertys M; Mokry J (Acta Medica Martiniana, 2020)
Tuberculosis is an airborne infectious disease that remains a huge global health-related issue nowadays. Despite constant approvals of newly developed drugs, the use of first-line antituberculosis medicines seems reasonable in drug-susceptible Mycobacterium tuberculosis strains. Therapeutic drug monitoring presents a useful technique for the determination of plasma drug concentration to adjust appropriate dose regimes. In tuberculosis treatment, therapeutic drug monitoring is aiding clinicians in selecting an optimal therapeutic level, which is essential for the personalisation of therapy. This review is aimed at clarifying the use of therapeutic drug monitoring of the first-line antituberculosis drugs in routine clinical practice.